أثر تطبيق إدارة علاقات الزبائن على الأداء التسويقي دراسة حالة للمؤسسة الخدمية موبيليس الأغواط - قريشي آسيا; التاوتي عبد العليم (جامعة عمار ثليجي الاغواط, 2022)
This study aimed to know the effect of relationship management dimensions on marketing performance at Mobilis Corporation – Laghouat-. The study data was collected through a questionnaire designed for this purpose, and to test the study hypotheses, a set of statistical methods were used, and after using the multiple linear regression method, it was confirmed that there is a statistically significant effect. At the level (α≤ 0.05) of the dimensions of customer relationship management on marketing performance, as the main hypothesis test resulted in a statistically significant effect at the level (α≤ 0.05) of customer relationship management on the leveling performance.